2021
DOI: 10.1002/jmv.26803
|View full text |Cite
|
Sign up to set email alerts
|

Vascular liver injury mimicking an intrahepatic cholangiocarcinoma in a COVID‐19 patient

Abstract: To the Editor, The outbreak of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, responsible for coronavirus disease 2019 (COVID-19), has rapidly reached a pandemic spreading.Contagion mainly occurs through the upper respiratory tract that is often involved in early disease, and pulmonary damage is the main cause of death. Nevertheless, SARS-CoV-2 can virtually localize in every organ, engendering site-specific damage. 1 COVID-19 complications due to the prothrombotic potential associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The patient's SARS-CoV-2 test was also found to be positive and the authors suggested the possibility of AIH flare in this setting. Two other cases have been described in the setting of COVID-19 presenting with symptoms and workup resembling cholangiocarcinoma attributed to viralinduced cholangiopathy and portal vessel damage [24,26]. Finally, recent articles evaluating long COVIDassociated GI symptoms/conditions have proposed alternate mechanisms for their occurrence, such as residual replicative virus particles in GI and hepatic tissues, changes in the gut microbiome, and autoimmune processes, resulting in autonomic dysfunction including POTS-like presentations and/or GERD [19,20,27].…”
Section: Discussionmentioning
confidence: 99%
“…The patient's SARS-CoV-2 test was also found to be positive and the authors suggested the possibility of AIH flare in this setting. Two other cases have been described in the setting of COVID-19 presenting with symptoms and workup resembling cholangiocarcinoma attributed to viralinduced cholangiopathy and portal vessel damage [24,26]. Finally, recent articles evaluating long COVIDassociated GI symptoms/conditions have proposed alternate mechanisms for their occurrence, such as residual replicative virus particles in GI and hepatic tissues, changes in the gut microbiome, and autoimmune processes, resulting in autonomic dysfunction including POTS-like presentations and/or GERD [19,20,27].…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that the embolic sprouting of floating aortic thrombi caused splenic ischemic lesions. 12 A retrospective study on 12 patients that recovered from severe COVID-19 with serum ALP of three times upper than the normal limit showed that 92% (11/12) of them had a beaded appearance of intrahepatic ducts in MRCP. Unfortunately, five patients who experienced constant jaundice, liver insufficiency, and frequent bacterial cholangitis had been referred for liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…However, a liver biopsy showed an inflammatory lesion described by plasma cellular infiltrates and portal‐based confluent lymphohistiocytosis. It was hypothesized that the embolic sprouting of floating aortic thrombi caused splenic ischemic lesions 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation